Factors Affecting Low Birth Weight During the 2020-2021 Pandemic Period at the Yogyakarta City Regional General Hospital - Meilani Dwi Astuti; Istri Bartini; Riadini Wahyu Utami; Ari Andriyani (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
Background: Coronavirus Disease 2019 (COVID-19) is a new type of disease that has never been identified in humans before. COVID-19 can be transmitted from human to human through coughing/sneezing droplets. People most at risk of contracting this disease are people who have close contact with COVID-19 patients, including those caring for COVID-19 patients (RI Ministry of Health, 2020). Low Birth Weight (LBW) is a baby born weighing the same or less than 2500 grams (WHO, 2014). Low birth weight newborns have a higher risk of death in the first 28 days of life. (Jornayvaz, 2016). This study aims to determine what factors can influence the incidence of LBW in Yogyakarta City Hospital. Based on the results of a preliminary study at the Yogyakarta City Hospital in January-December 2020, data on LBW babies were 43. While the data obtained in 2021 in January-December LBW data is 48 babies. Research Method: this research is a quantitative analytical descriptive study with a cross sectional approach. This research was conducted at the Yogyakarta City Hospital. The population in this study were all pregnant women who gave birth to LBW babies. Determination of the sample using a total sample of 72 people. Results: The results showed that the majority of respondents were aged 20-29 years, with 37 respondents (51.4%), last mother's education, the majority being high school, 38 respondents (52.8%), mother's occupation as housewife, 30 respondents (41.7%) , The highest maternal parity G1 was 33 respondents (45.8%), the sex of the baby, the majority of weight was female, 41 respondents (56.8%), the most gestational age 37 weeks, 43 respondents (59.7%), anemia in pregnant women 11 gr (51.4%), the most gestational interval 2 years was 41 respondents 56.9%, and the causes of LBW and LBW were most common in KPD as many as 24 (33.3%). Conclusion: the results of the study show that of the 9 factors, there are 6 factors that influence the incidence of LBW, namely education, occupation, sex of the baby, anemia, disease and pregnancy complications.